2015
DOI: 10.3167/nc.2015.100106
|View full text |Cite
|
Sign up to set email alerts
|

Legal Pluralism, Forest Conservation, and Indigenous Capitalists: The Case of the Kalanguya in Tinoc, the Philippines

Abstract: The Philippines is one of the many countries that currently acknowledge the presence of indigenous peoples (IPs) within their territories. This acknowledgment often comes with a formal recognition of the rights of IPs, including the right to practice their customary laws. Because of the equal existence of overarching state laws, this formally leads to a situation of legal pluralism for IPs. For many forest conservation advocates, legal pluralism for IPs, particularly with regard to land ownership and forest ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this view, market mechanisms aligned with economic incentives ensure conservation; otherwise, Indigenous Peoples would join those who exploit the forest without environmental concern (Lu Holt 2005). For instance, Albano et al (2015), using a long historical perspective, found that the Kalanguya people in the Philippines have practiced both destructive and nondestructive land use, acting as market players (Albano et al 2015).…”
Section: Protected Areas and Indigenous Rightsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this view, market mechanisms aligned with economic incentives ensure conservation; otherwise, Indigenous Peoples would join those who exploit the forest without environmental concern (Lu Holt 2005). For instance, Albano et al (2015), using a long historical perspective, found that the Kalanguya people in the Philippines have practiced both destructive and nondestructive land use, acting as market players (Albano et al 2015).…”
Section: Protected Areas and Indigenous Rightsmentioning
confidence: 99%
“…The gap between global discourses and actual conservation arrangements responds to the different images of Indigenous Peoples' relationship with nature deployed by international actors, Indigenous movements, and national authorities. These images navigate between conceiving Indigenous communities as market players (Albano et al 2015) who need economic incentives to keep them from joining illegal loggers (Zaitchik 2018) and conceiving them as forest stewards whose interests align with environmental protection (De Bont 2015;Lu Holt 2005;Reimerson, 2013).…”
mentioning
confidence: 99%